Elusive Safety: The New Geography of Capital Flows and Risk - Laura Alfaro; Ester Faia; Ruth Judson; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2020)
Using a unique confidential data set with industry disaggregation of official U.S. claims and liabilities, we find that dollar-denominated securities are increasingly inter-mediated by tax havens financial centers (THFC) and by less regulated funds. These securities are risky and respond to tax rates and prudential regulations, suggesting tax avoidance and regulatory arbitrage. Issuers are mostly intangible-intensive multinationals, that can more easily move across borders. Investors require a high Sharpe ratio, suggesting search for yield. In contrast, safe treasuries are mainly held by the foreign official sector and increased with quantitative easing policies. Facts on the privately held securities are rationalized through a model where multinationals with heterogeneous default probabilities endogenously choose to shift profits to a THFC against a cost and are funded by global intermediaries with endogenous monitoring intensity. A fall in debt costs, due to an increase in global savings channeled by low regulated intermediaries, raises firms' profits. More firms can afford to enter the THFC and, as they appear elusively safer, intermediaries reduce monitoring intensity, increasing ex post risk.
Keywords: F10; F20; 330; tax havens; geography of flows; profit shifting; tax avoidance; risk; safe assets; endogenous entry